Methoprene-Tolerant (Met) Is Indispensable for Larval Metamorphosis and Female Reproduction in the Cotton Bollworm Helicoverpa armigera - Ma, Long; Zhang, Wanna; Liu, Chen; Chen, Lin; Xu, Yang; Xiao, Haijun; Liang, Gemei (Frontiers in Physiology, 2018)
Juvenile hormone (JH) represses larval metamorphosis and induces adult reproduction in insects. Methoprene-tolerant (Met) is identified as an intranuclear receptor that mediates JH actions. In the present study, we characterized a Met from the severe agricultural pest, Helicoverpa armigera, namely HaMet. In the larval stage, HaMet is predominantly expressed in the epidermis and midgut, and is upregulated before each molting, whereas in adults HaMet is maximally expressed in the ovary, testis, and fat body. The immunofluorescence assay revealed that HaMet was distributed in the longitudinal and circular muscle layers of midgut in larvae, whereas in the ovary of female adults, HaMet was localized in the nucleus of the oolemma. Knockdown of HaMet in final-instar larvae shortened the time of pupation, induced abnormal pupation, and dampened pupation rate. In female adults, HaMet depletion severely suppressed the transcription of Vitellogenin (Vg) and Vitellogenin Receptor (VgR), disrupted the Vg accumulation in fat body and the yolk protein uptake in oocytes, and finally led to an impaired fecundity. Our findings therefore confirmed that HaMet acted as a nuclear receptor of JH and played an essential role in larval metamorphosis, vitellogenesis, and oocyte maturation.